Cross Province Analysis of Indonesian Islamic Banking Financing - Faizul Mubarok; Rusdianto Rusdianto (Jurnal Ilmiah Ekonomi Islam, 2022)
The economic development of a country cannot be separated from the role of the banking sector in carrying out its function as an intermediary financial institution for people in need. Islamic banks need to create a financing portfolio to effectively and efficiently by considering the influential variables. This study aims to analyze the factors that influence Islamic bank financing in the province of Java. This study uses a fixed-effect model and annual data from 2010 to 2021. The study results found that total assets, liquidity, and exchange rates affected Islamic banking financing in the province of Java, while the province's economic growth had no effect. Islamic banking needs to carry out a provincial financing portfolio in order to facilitate the process of distributing financing to each province.